Penerapan Proses Akuntansi Menggunakan Microsoft Excel Dalam Penyusunan Laporan Keuangan Pada Perusahaan Sinar Harapan - Triandi, Triandi; Stephanie, Thresia (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2010)
This research has purpose: to maximize Microsoft Excelâs function, to facilitate every division in order to be more efficient and effective in carrying out its function, and to facilitate in arranging finance accounting and also in transaction recording at Sinar Harapan Company. The research was done at Sinar Harapan Company located in Palembang. Sinar Harapan Company is a distributor company of lubricating oil. The result of this research shows that recording and selling system at Sinar Harapan Company remains using simple system. Besides that, its accountancy recording keeps using manual entry or manual bookkeeping, after that copied to Microsoft Excel. The weakness of manually system is the processing will be slow-moving, and then it needs so much time and energy. The information yielded canât be guaranteed accurately because itâs done by human being, so the risk of being false will be high. Accounting process by means of Microsoft Excel in arranging finance accounting is intended to maximize Microsoft Excelâs functions. The strength of computerized processing is data processing can be more speedy, the information yielded will be more accurate, and its working process will be more efficient and more effective. Keywords : Accounting process; Finance report arranging